Improving Institutional Capability and Financial Viability to Sustain Transport : An Evaluation of World Bank Group Support since 2002 - Independent Evaluation Group (Washington, DC: World Bank, 2013)
The services provided by investments in road networks, railways and transit systems, and ports for trade by air and water are important contributors to poverty alleviation and economic growth. Sustained transport investments can support poverty reduction directly, in terms of improving access and thus economic opportunity targeted to the rural poor, and through facilitating broad-based growth. But the impact of infrastructure investments and the services that arise from them can be undermined by poor operations and maintenance. The objective of this evaluation is to assess the effectiveness of Bank group support to countries in sustaining the provision of transport infrastructure and services and to distill lessons on the factors contributing to sustained transport. In the context of this evaluation sustained provision of infrastructure and services is defined as the extent to which the policies, institutional and regulatory framework, sector management capacity, and financial arrangements are in place to ensure that transport infrastructure is operated and maintained, enabling a reliable flow of services over the long term. The term transport is used throughout this report to mean transport infrastructure and services, unless otherwise specified.